2014
DOI: 10.1111/ecc.12171
|View full text |Cite
|
Sign up to set email alerts
|

Accessing cancer services in North West England: the Chinese population

Abstract: Relatively few Chinese patients access tertiary cancer services in North West England. We investigated the reasons behind this using a culturally sensitive questionnaire. The questionnaire, completed by 214 Chinese people in English, Cantonese or Mandarin, evaluated the Chinese population's access and satisfaction with primary care, understanding of cancer and awareness of local cancer services. Ninety-five per cent of respondents were registered with a general practitioner (GP) and 75% had accessed primary ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…However, Chinese people who dwell in China town were less likely to have yearly check-ups than Chinese people who live outside of Chinatown [22]. Among Chinese community, even if they get health insurance, they might not use it, Chinese women who live in China town, under the patriarchal tradition, may not want to be seen by doctors to start with, not alone getting detected of domestic violence [23]. In another words, Chinese women who dwell in big cities should get their health insurance and check-ups and start lives out of Chinese community.…”
Section: The Right Place To Dwellmentioning
confidence: 99%
See 2 more Smart Citations
“…However, Chinese people who dwell in China town were less likely to have yearly check-ups than Chinese people who live outside of Chinatown [22]. Among Chinese community, even if they get health insurance, they might not use it, Chinese women who live in China town, under the patriarchal tradition, may not want to be seen by doctors to start with, not alone getting detected of domestic violence [23]. In another words, Chinese women who dwell in big cities should get their health insurance and check-ups and start lives out of Chinese community.…”
Section: The Right Place To Dwellmentioning
confidence: 99%
“…This phenomenon prevails all over the world. A survey done in North West England showed that Chinese people underused screening www.opastonline.com programs and tertiary cancer services even if they have medical insurances [23].…”
Section: The Right Place To Dwellmentioning
confidence: 99%
See 1 more Smart Citation
“…Conway et al . (; pp. 570–581) examine patterns of accessing services in the North West of England and describe some important patterns relating to this significant sub‐group of the population.…”
mentioning
confidence: 99%
“…An increase in research investigating psychosocial concerns is also evident (Chambers et al 2013b). Conway et al (2014;pp. 570-581) examine patterns of accessing services in the North West of England and describe some important patterns relating to this significant sub-group of the population.…”
mentioning
confidence: 99%